POLA PENANGANAN GURU MENGHADAPI BULLYING PADA ANAK USIA DINI (STUDI KASUS DI RA RAUSHAN FIKR TANGERANG SELATAN) - Hasanah; Mia Istiqomah (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This research was motivated by direct experience of seeing cases of bullying at school during the Field Experience Program (PLP). This experience inspired us to dig deeper into teachers' effective handling patterns in dealing with bullying cases. The aim of this research is to instill teachers' handling patterns in dealing with bullying in early childhood and to find out what factors support and hinder teachers in handling bullying at RA Raushan Fikr, South Tangerang. This research uses descriptive qualitative, the researcher attempts to describe the activities studied on certain objects clearly and systematically. The main research data sources are the school principal, class B teacher, class B teacher. Secondary data sources include books, journals, previous theses. The results of this research are (1) Treatment pattern: the teacher provides special assistance with a careful and loving approach, counseling and protection, the teacher provides clear rules and direction for children regarding expected and unexpected behavior in the classroom. The teacher conducts an evaluation after providing assistance. (2) Supporting and inhibiting factors: teacher awareness about bullying, good communication skills, and school policy support. The obstacle is the lack of cooperation between parents and the school, lack of education about bullying.